Гидромашины с циклоидальной формой вытеснителей, применяемые в силовых гидроприводах мобильной техники - Панченко, Анатолий Иванович; Панченко, Анатолій Іванович; Panchenko, Anatolii; Волошина, Анжела Анатольевна; Волошина, Анжела Анатоліївна; Voloshyna, Anzhela (My University, 2012)
The work is devoted to planetary hydraulic machines classification with it’s main design philosophy: type of displacer movement, mode of planetary displacer movement compensation and working fluid distribution.
Planetary hydraulic machines with cycloidal displacers, which are used in mobile machinery power hydraulic drives
Keywords: мобильная техника; гидрофикация; силовые гидроприводы; планетарные гидромашины; героторные гидромашины; гидравлическое поле; схемы компенсирования; компенсирование планетарного движения вытеснителей